2014
DOI: 10.1016/j.ijsu.2014.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Early biomarkers of hypocalcemia following total thyroidectomy

Abstract: Hypocalcemia is the most frequent major complication following total thyroidectomy (TT), delaying timely hospital demission. We prospectively evaluated the diagnostic utility of parathyroid hormone (PTH) measured one hour after TT and the delta (post-minus pre-surgery) PTH in order to determine which biomarker best predicted post-surgery hypocalcemia. Ninety-six consecutive patients, with either plurinodular goiter, Graves' disease or cervico-mediastinal goiter (22 (23%) men and 74 (77%) women, mean age 48.5 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 15 publications
0
7
1
2
Order By: Relevance
“…Low post-operative PTH was found to have a statistically significant association with transient biochemical hypocalcaemia in 24 studies, 1033 compared with 3 studies where there was not a statistically significant result 34–36 . Low intra-operative PTH levels and a larger differential PTH from the pre-operative to post-operative stage were also seen to have statistically significant associations in 2 studies 37,38 and 13 studies 10,12,14,15,22,23,27,29,31,36,39–41 , respectively. Pre-operative PTH showed a non-significant association with transient biochemical hypocalcaemia in the majority of studies.…”
Section: Resultsmentioning
confidence: 81%
“…Low post-operative PTH was found to have a statistically significant association with transient biochemical hypocalcaemia in 24 studies, 1033 compared with 3 studies where there was not a statistically significant result 34–36 . Low intra-operative PTH levels and a larger differential PTH from the pre-operative to post-operative stage were also seen to have statistically significant associations in 2 studies 37,38 and 13 studies 10,12,14,15,22,23,27,29,31,36,39–41 , respectively. Pre-operative PTH showed a non-significant association with transient biochemical hypocalcaemia in the majority of studies.…”
Section: Resultsmentioning
confidence: 81%
“…Moreover, it led to a much-improved follow-up to a possible radiometabolic treatment. However, side effects included definitive hypoparathyroidism and lesions of the inferior laryngeal nerve [10].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that PTH provides a sensitivity of up to 96.4% for predicting hypocalcemia, with a specificity of 37.5-75%, although other studies have reported values that approached 100% [1,8] . We believe that these results are related to the larger patient populations from those studies, and it should be noted that mild hypocalcemia can occur even if there are normal postoperative PTH levels [10] . This is especially true in cases of vitamin D deficiency, as proposed by Pradeep et al [11] .…”
Section: Discussionmentioning
confidence: 78%